The Civil Society of Ancient Rome - Anvar , Allamuratov (Pubmedia Social Sciences and Humanities, 2024)
The article explores the Roman concept of civitas, which defined their society as a civil collective bound by shared rights, duties, politics, religion, and ideology. Cicero described civitas as encompassing common laws, justice, and social ties. Unlike Greek polis, Roman citizenship was managed by high magistrates like the censor, emphasizing a hierarchical structure. Roman voting operated on a "one centuria - one vote" principle, differing from the Greek model, and Romans extended more rights to outsiders. Land ownership linked citizenship, with communal land (ager publicus) available for rent. The city boundary (pomerium) had religious importance, protecting civic life. The Romans valued freedom (libertas) and upheld collective values like dignity, courage, and piety. Ancestral customs (mores maiorum) and historical memory were central, maintained through ceremonies and funerary traditions. Debate exists on whether the Roman civitas was a state, with differing views across German, Anglo-American, and Southern European historians. Scholars also disagree on how long the civitas remained a polis-like entity, with opinions ranging from its decline in the 1st century BC to its influence in the Mediterranean empire.